Terrorism and organized hate crime intelligence gathering, analysis, and investigations - Ronczkowski, Michael (CRC Press, Taylor & Francis Group, 2018)
The ability of law enforcement agencies to manage and act upon intelligence is the key to countering terrorism. Likewise, a critical foundation of intelligence-led policing is the proper analysis of all information gained. Terrorism and Organized Hate Crime: Intelligence Gathering, Analysis, and Investigations, Fourth Edition demonstrates how to recognize the indicators of an impending act of terrorism or mass violence, how to deter an attack, and how to transform information into intelligence to meet community demands for safety and security.